Evaluación y caracterización del impacto del tiempo de backoff en la red de acceso radio de IoT celular con tráfico masivo - Santander González, Daniel Alejandro (2021)
The large-scale deployment of Machine-Type Communications (MTC) over the cellular radio access network allows many devices to compete for network resources to offer various services. They are causing collisions in the random-access channel. The backoff procedure is a technique used for collision resolution by assigning a waiting time before transmission. This timeout is determined by the base station through the Backoff Indicator (BI) and is chosen randomly by the devices based on the configured BI. The present research work evaluates and characterizes the impact of changing the BI values under different bulk traffic scenarios by using performance metrics such as the probability of successful access, access delay, and the average number of preamble transmissions. For this purpose, a simulation model of the random-access procedure based on contention was developed using Matlab software and considering the specifications of the Third Generation Partnership Project (3GPP) standardization body. Based on the results obtained, an optimal range of BI values was characterized by meeting different reliability conditions for each scenario. With a suitable configuration of the RACH parameters, a successful access probability greater than 85% is achieved with a moderate increase in access delay, which is considered ideal for delay-tolerant applications in scenarios with massive traffic.